“Remember to Hand Out Medals”: Peer Rating and Expertise in a Question-and-Answer Study Group - Ponti, Marisa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This article reports on an exploratory study of giving medals as part of a peer rating system in a question-and-answer (Q&A) study group on Python, a programming language. There are no professional teachers tutoring learners. The study aimed to understand whether and how medals, awarded to responses in a peer-based learning environment, can work as a mechanism to assess the value of those responses when traditional markers of expertise are not always clearly defined and identifiable. Employing a mixed-method approach, the analysis examined (a) the content of the answers that were awarded medals and their perceived immediate value and (b) the nature of the networked relationships resulting from participants’ interactions. The findings suggest that the peer rating system makes visible what the participants find immediately valuable and allocates a form of recognition that extends the “legitimation code”, which refers to the credentials that make someone competent and worthy of recognition.